IDENTIFIKASI JENIS PIGMEN DAN UJI POTENSI ANTIOKSIDAN EKSTRAK PIGMEN BAKTERI Rhodococcus sp HASIL ISOLASI DARI SEDIMEN SUMBER AIR PANAS GEDONG SONGO - Muhamad Fikri Zulfikar; Endang Kusdiyantini; Siti Nur Jannah (Jurnal Akademika Biologi, 2017)
Pigments are the coloring agents commonly used in the pharmaceutical, cosmetic, and food industries. This compound has the ability as antibacterial, anticancer, antibiotic and antioxidant. Pigment can be obtained synthetic and natural, natural pigments can be produced by plants, animals and microbes, one of which microbes is Rhodococcus sp. This study was conduct to identify the pigment found in Rhodococcus sp and measure the antioxidant activity of pigment produced by Rhodococcus sp. Growth and pigments production Rhodococcus sp was  grown on NB (Nutrient broth) medium with 96 hours incubation. This Growth was measured by dry weight cell. Identification of pigment using Thin Layer Chromatography and spectrophotometer UV-Vis. Measured of antioxidant activity Rhodococcus sp pigment using Carotene Bleaching methods. The results of pigments obtained from the identification by separation of pigment samples by thin layer chromatography resulted in 2 fractions on silica gel plate GF 250 with Rf values of 0.75 and 0.90. and analysis of UV-Vis spectrophotometers obtained optimum wavelengths 395 and 420 nm is beta-carotene pigments. Rhodococcus sp pigment measured its antioxidant activity with carotene bleaching method with the antioxidant activity value 51,24%.Keywords: Pigment, Rhodococcus sp, Pigment identification, antioxidant activity